Comparison of Microstructures and Magnetic Characteristics of CoFe2O4/PEG and MnFe2O4/PEG for Drug Delivery System Application - Joko Utomo; Hafiz Sub’han (Universitas Sultan Ageng Tirtayasa, 2024)
CoFe2O4/PEG and MnFe2O4/PEG materials have been successfully prepared using the coprecipitation method with a synthesis temperature of 90 °C. Doxorubicin (DOX) was successfully loaded and released in both samples. Based on the XRD results, the crystal structure of CoFe2O4/PEG is cubic spinel while the structure of MnFe2O4/PEG is hematite with the lattice parameters for CoFe2O4/PEG and MnFe2O4/PEG is 8.40 nm and 8.41 nm, respectively. Based on the SEM results, the morphology of the two samples is quite homogenous and the particle size of CoFe2O4/PEG is smaller than MnFe2O4/PEG’s. There is a vibrational spectrum of Fe – O in both samples at wave numbers of 600 - 690 cm-1. Based on VSM characterization, CoFe2O4/PEG is included in hard magnetic materials with a saturation magnetization of 54.85 emu/g and coercivity of 788 Oe. Meanwhile, MnFe2O4/PEG is classified as soft magnetic materials with lower saturation magnetization of 11 emu/g and coercivity of 7.42. In addition, based on the UV-Vis characterization obtained the efficiency of drug loading of CoFe2O4/PEG is higher (98.8 %) than the MnFe2O4/PEG sample (96.3 %). It is the opposite for the drug release percentage that CoFe2O4/PEG has 30.6 % which is lower than the MnFe2O4/PEG (51.6 %).